2013
DOI: 10.1186/1471-2458-13-177
|View full text |Cite
|
Sign up to set email alerts
|

A motivational interviewing intervention to PREvent PAssive Smoke Exposure (PREPASE) in children with a high risk of asthma: design of a randomised controlled trial

Abstract: BackgroundEspecially children at risk for asthma are sensitive to the detrimental health effects of passive smoke (PS) exposure, like respiratory complaints and allergic sensitisation. Therefore, effective prevention of PS exposure in this group of vulnerable children is important. Based on previous studies, we hypothesized that an effective intervention program to prevent PS exposure in children is possible by means of a motivational interviewing tailored program with repeated contacts focussing on awareness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…In our population we reported a weak association between a marker of the mechanical pathway (ERV% predicted) with BMI-SDS, but no association between a marker of the inflammatory pathway (leptin) with BMI-SDS. In order to avoid the trend in the control group that parents/children look for weight reduction measures, a randomized consent design may be more appropriate for future RCTs on this topic [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our population we reported a weak association between a marker of the mechanical pathway (ERV% predicted) with BMI-SDS, but no association between a marker of the inflammatory pathway (leptin) with BMI-SDS. In order to avoid the trend in the control group that parents/children look for weight reduction measures, a randomized consent design may be more appropriate for future RCTs on this topic [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-five full-text articles were read. Forty-five studies were excluded for the following reasons: no relevant outcomes, 18 studies [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] ; the trial did not include a control group, 7 studies [56][57][58][59][60][61][62] ; the interventions were not aimed at parents of young children, 3 studies [63][64][65] ; the reporting period was ,1 month, 2 studies 66,67 ; data necessary for analysis were missing, 10 studies [68][69][70][71][72][73][74][75][76][77] ; the paper was a review article, 1 study 78 ; the article was a protocol, 2 studies 79,80 ; the article was a follow-up of a previous study, 1 study 81 ; there was no true control group (eg, 2 active interventions were compared), 1 study 82 .…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Of the non-smokers, 53.2 % were exposed to second-hand smoke in their homes [51•]. Several intervention trials have targeted tobacco smoke cessation and reduction of second-hand smoke exposure in the home [52, 53, 54•, 55]. However, a Cochrane review found that most intervention studies aimed at reducing children’s ETS exposure were ineffective [56].…”
Section: Environmental Tobacco Smokementioning
confidence: 99%